The Rhetoric of Policy Relevance in International Economics - William Milberg (Levy Economics Institute of Bard College, 1994)
This paper addresses the link between the generation of economic knowledge and economic policy conclusions. Focusing on the case of research in international trade, I establish a taxonomy of rhetorical practices used to make such a link. The flexibility observed in these practices contrasts markedly with the rigidity of the conventions of theoretical and empirical knowledge creation. A survey of articles on international trade from four major journals from 1988-1992 shows that most policyrelevant research is entirely theoretical, but the incidence of rhetorical practices depends on the nature of the research method (theoretical or empirical), and the journal in which the research is published. The survey data support the view that the flexiblity of rhetorical practices is integral to the legitimation of the knowledge generated by international trade economists.
Keywords: B41; F13; 330; Rhetoric; methodology; trade policy; new international economics; epistemology